Structural and biological engineering of 3D hydrogels for wound healing - Mohammad Hadi Norahan; Sara Cristina Pedroza-González; Mónica Gabriela Sánchez-Salazar; Mario Moisés Álvarez; Grissel Trujillo de Santiago (Bioactive Materials, 2023)
Chronic wounds have become one of the most important issues for healthcare systems and are a leading cause of death worldwide. Wound dressings are necessary to facilitate wound treatment. Engineering wound dressings may substantially reduce healing time, reduce the risk of recurrent infections, and reduce the disability and costs associated. In the path of engineering of an ideal wound dressing, hydrogels have played a leading role. Hydrogels are 3D hydrophilic polymeric structures that can provide a protective barrier, mimic the native extracellular matrix (ECM), and provide a humid environment. Due to their advantages, hydrogels (with different architectural, physical, mechanical, and biological properties) have been extensively explored as wound dressing platforms. Here we describe recent studies on hydrogels for wound healing applications with a strong focus on the interplay between the fabrication method used and the architectural, mechanical, and biological performance achieved. Moreover, we review different categories of additives which can enhance wound regeneration using 3D hydrogel dressings. Hydrogel engineering for wound healing applications promises the generation of smart solutions to solve this pressing problem, enabling key functionalities such as bacterial growth inhibition, enhanced re-epithelialization, vascularization, improved recovery of the tissue functionality, and overall, accelerated and effective wound healing.